Improving Students’ Speaking Ability Through Demonstration Method : (A Case Study of Junior High School Students) - Yusridawati, Yusridawati (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
This study is a case study for Class IX-1 Students of SMP Negeri 12 Lhokseumawe. Through learning procedure text, students can improve their ability in speaking English by demonstrating how to do something. This study uses a qualitative approach to obtain data and analysis through reflective and participatory studies. Program development is based on data and information from students and teachers through two stages of the classroom action research cycle. In the first cycle, students were seen to be quite active in learning. From the observation, it was found that student activity reached 77%. Furthermore, in the second cycle, student activity continued to increase until it reached 86% so that it increased by 9%. The increase in student activity was followed by an increase in learning outcomes, namely in the first cycle the average value was only 69, increasing to an average of 75 in the second cycle. From the implementation of CAR in cycles I and II, it can be concluded that through the application of the demonstration method, it can improve student achievement in learning English in class IX-1 of SMP Negeri 12 Lhokseumawe.